2018
DOI: 10.1002/hed.25516
|View full text |Cite
|
Sign up to set email alerts
|

Novel ANO5 mutation c.1067G>T (p.C356F) identified by whole genome sequencing in a big family with atypical gnathodiaphyseal dysplasia

Abstract: Background: Gnathodiaphyseal dysplasia (GDD) is a rare skeletal disorder that has not been well studied. Methods: Sanger sequencing, whole-genome sequencing (WGS), and bioinformatics and structural modeling analyses were performed. Results: A family with patients with fibro-osseous lesions of the jawbones were initially diagnosed with cherubism. Sequencing of SH3BP2, which is the causal gene of cherubism, revealed no pathogenic mutation. Through WGS, we identified a novel mutation c.1067G>T (p.C356F) in ANO5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…(8)(9)(10)(11) Heretofore, 11 missense mutations in the ANO5 gene have been identified to be associated with GDD from various races and ethnicities. (7,(12)(13)(14)(15)(16)(17)(18) Two of them, C356R and C356G, were first reported in a large Japanese family and resulted in reduced cell adhesion and more rounded cell morphology owing to the regulation of intracellular calcium homeostasis. (7) The T513I mutation in ANO5 protein caused a gain of function enabling CaCCs and phospholipid scrambling at low cytosolic Ca 2+ levels.…”
Section: Introductionmentioning
confidence: 99%
“…(8)(9)(10)(11) Heretofore, 11 missense mutations in the ANO5 gene have been identified to be associated with GDD from various races and ethnicities. (7,(12)(13)(14)(15)(16)(17)(18) Two of them, C356R and C356G, were first reported in a large Japanese family and resulted in reduced cell adhesion and more rounded cell morphology owing to the regulation of intracellular calcium homeostasis. (7) The T513I mutation in ANO5 protein caused a gain of function enabling CaCCs and phospholipid scrambling at low cytosolic Ca 2+ levels.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the similarities in the clinicopathological features and genetic alterations between GDD and FGC, we suggest that FGC may be an atypical subtype of GDD, which may have no systemic symptoms, classic long bone curvature, and cortical thickening, with fibro-osseous lesions of the jawbone as the only obvious symptoms. Other studies have also reported atypical cases of GDD where the patient's age of onset, the extent of expansion, and pathological and imaging manifestations also overlap with those of FGC (Andreeva et al, 2016;Zeng et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…However, whether FGC and GDD are genetically related remains unclear. Recently, a missense mutation in ANO5 (also known as TMEM16E) was identified in GDD and was considered a suspected causative mutation for GDD (Duong et al, 2016;Jin et al, 2017;Marconi et al, 2013;Mizuta et al, 2007;Otaify et al, 2018;Tsutsumi et al, 2004;Zeng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous types of identified variants in ANO5 are available at HGMD®. Zeng et al ( 2019 ) have reported a novel mutation c.1067G>T (p.C356F) in ANO5 which is the causes of GDD. This mutation has been specified as a deleterious variant by bioinformatics analyses and structural modeling.…”
Section: Discussionmentioning
confidence: 99%